Immunosuppression With CD40 Costimulatory Blockade Plus Rapamycin for Simultaneous Islet–Kidney Transplantation in Nonhuman Primates. Issue 3 (6th September 2016) - Oura, T.; Hotta, K.; Lei, J.; Markmann, J.; Rosales, I.; Dehnadi, A.; Kawai, K.; Ndishabandi, D.; Smith, R.‐N.; Cosimi, A. B.; Kawai, T.
Abstract : The lack of a reliable immunosuppressive regimen that effectively suppresses both renal and islet allograft rejection without islet toxicity hampers a wider clinical application of simultaneous islet–kidney transplantation (SIK). Seven MHC‐mismatched SIKs were performed in diabetic cynomolgus monkeys. Two recipients received rabbit antithymocyte globulin (ATG) induction followed by daily tacrolimus and rapamycin (ATG/Tac/Rapa), and five recipients were treated with anti‐CD40 monoclonal antibody (mAb) and rapamycin (aCD40/Rapa). Anti‐inflammatory therapy, including anti–interleukin‐6 receptor mAb and anti–tumor necrosis factor‐α mAb, was given in both groups. The ATG/Tac/Rapa recipients failed to achieve long‐term islet allograft survival (19 and 26 days) due to poor islet engraftment and cytomegalovirus pneumonia. In contrast, the aCD40/Rapa regimen provided long‐term islet and kidney allograft survival (90, 94, >120, >120, and >120 days), with only one recipient developing evidence of allograft rejection. The aCD40/Rapa regimen was also tested in four kidney‐alone transplant recipients. All four recipients achieved long‐term renal allograft survival (100% at day 120), which was superior to renal allograft survival (62.9% at day 120) with triple immunosuppressive regimen (tacrolimus, mycophenolate mofetil, and steroids). The combination of anti‐CD40 mAb and rapamycin is an effective and nontoxic immunosuppressive regimen that uses only clinically available agents for kidney and islet recipients. Abstract : In this preclinical study, authors identify the combination of anti‐CD40 monoclonal antibody and rapamycin as an effective and nontoxic immunosuppressive regimen for simultaneous islet–kidney transplantation.